Domestic Pigs as an Animal Model of Myocardial Infarction: a Comparison of Systolic and Diastolic Blood Flow Velocities of Cardiac Valves - Fitri, Arni Diana; Subangkit, Mawar; Esfandiari, Anita; Gunanti; Noviana, Deni (Acta VETERINARIA Indonesiana, 2025)
Cardiovascular disease (CVD) is still the leading cause of death according to WHO in 2021. CVD generally results in myocardial infarction (MI), which occurred after tissue ischemia. Echocardiography is most likely a diagnostic tool without invasive effects. This study aimed to compare the blood flow in pig research animals treated with ligases of the circumflex arteries. Measurements were made in the mitral valve (MV), tricuspid valve (TV), semilunar pulmonary valve (SLP), and semilunar aortic valve (AO) of velocity during systole (Vs), velocity during diastole (Vd), time average peak velocity (TAMAX), and blood flow pressure at three-time points: before ligase treatment, after acute infarction (60 min), and 8 weeks after ligase treatment. All parameters in MV group increased at 60 min and decreased at 8th weeks. On TV, TAMAX and pTAMAX decreased at 60 min and week 8. In SLP, VS, pVS, and Vd decreased at 60 min and increased at 8th week. The pVd and pTAMAX parameters decreased at 60 min and 8th week, while TAMAX increased at 60 min and decreased at 8th week. In AO, the TAMAX and pTAMAX parameters increased at 60 min and 8 weeks; the other parameters were similar to MV and TV patterns.